Career Confidence Improvement Module Through CBT For 12th Grade High School Students - Ayuningtyas, Luluk; Isriyah, Mudafiatun; Mawaddati, Ika Romika (IAIN Kudus, 2024)
Career Confidence Improvement Module Through Cbt For 12th grade High School Students. This study aims to develop a module to increase self-confidence in career choices through cognitive behavioral therapy (CBT) to overcome concerns about success for 12th grade students at MAN 2 Jember Dormitory. Concerns about the future and career success are often factors that hinder students from making the right career decisions. Cognitive behavioral therapy (CBT) was chosen as an intervention approach because of its effectiveness in changing negative mindsets and increasing self-confidence. The research method used is quantitative with a Research and Development (R&D) approach involving several stages, starting from needs analysis, design, expert validation, to limited trials. The results of the study showed that this module was effective in increasing students' self-confidence in making career choices and reducing their concerns about future success. Students who took this module experienced positive changes in their thinking and behavior related to their career choices and their future. Thus, this module is expected to be one of the solutions to help 12th grade students at MAN 2 Jember in facing challenges in determining their career choices.Keywords: Module, Self-Confidence, Career, CBT, Students